Case report: A comatose patient with pregabalin overdose successfully treated with continuous renal replacement therapy - Nielsen, Visti Torbjørn; Wijayasinghe, Nelun; Høgberg, Lotte Christine Groth; Bøgevig, Søren (Frontiers in Medicine, 2023)
Pregabalin (PB) overdose causes mild symptoms and coma is rarely seen unless the patient has also ingested sedatives and/or has preexisting renal disease. We present a case report of a suicide attempt with PB where the patient presented in a comatose state that was successfully treated with continuous renal replacement therapy (CRRT). Treatment of PB overdose is usually supportive. However, previous reports of PB overdose have been treated with intermittent hemodialysis (IHD) in patients with preexisting renal disease. The problem with IHD is that it is only available in specialist centers and unsuitable for unstable patients. In the following case report, the patient presented to the emergency department (ED) unconscious and hypotensive. It was thought that the patient tried to commit suicide by taking an overdose of zopiclone tablets, as empty packets of zopiclone tablets were found beside the patient. There was no effect with flumazenil treatment, so the patient was intubated, mechanically ventilated, and admitted to the intensive care unit (ICU) where inotropic support was started. Despite supportive therapy, there was no improvement in the patient’s condition. Further investigation into the patient’s medical records uncovered prescriptions of PB. Based on this finding, plasma PB levels were measured and found to be 20 times the upper limit of the therapeutic reference range. CRRT was instituted and after 6 h of treatment the patient woke up. Hospitals with ICUs often have CRRT available in their units whereas IHD is less readily available. This case report demonstrates that CRRT is an effective method for treating PB overdose in an unconscious unstable patient that was unsuitable for transfer to another hospital.